A new species of Fejervarya (Anura: Dicroglossidae) from Bangladesh - Howlader, Mohammad Sajid Ali (Zootaxa, 2011)
A new cryptic species of the genus Fejervarya is described from the Chittagong district of Bangladesh. Fejervarya asmati sp. nov. is compared with its morphologically similar and geographically proximate congeners. The species can be readily diagnosed by having the following combination of characters: SVL 29.1– 33.4 mm; butterfly shaped vocal marking present in male; forearm length 70% of hand length; relative length of fingers, shortest to longest: 2 < 4 < 1< 3; nostril much closer to snout tip than eye, nostril–snout length 57% of distance from front of eyes to nostril; nostril–snout length 0.67% of internarial distance; MBE 18% of HL.